If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 14 = 3(3x + 4) Reorder the terms: 14 + 10x = 3(3x + 4) Reorder the terms: 14 + 10x = 3(4 + 3x) 14 + 10x = (4 * 3 + 3x * 3) 14 + 10x = (12 + 9x) Solving 14 + 10x = 12 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 14 + 10x + -9x = 12 + 9x + -9x Combine like terms: 10x + -9x = 1x 14 + 1x = 12 + 9x + -9x Combine like terms: 9x + -9x = 0 14 + 1x = 12 + 0 14 + 1x = 12 Add '-14' to each side of the equation. 14 + -14 + 1x = 12 + -14 Combine like terms: 14 + -14 = 0 0 + 1x = 12 + -14 1x = 12 + -14 Combine like terms: 12 + -14 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 3n-9=13-5n | | 5x-7y=-9 | | 3x-16= | | -107x-7x=7x+19 | | 24x^2-47+20=0 | | x^2-7s=0 | | x^20-7s=0 | | (x-18)(x^2-36)=0 | | -6x^3-10x^2-6x=0 | | factorx^4+16= | | 12-4*(8-x)=20 | | x^4+16= | | 1/u+6=-6 | | -3(2s-3)-9=-2(7s+7)-2 | | x*y=1512 | | 10x-4x= | | 6timesx=4 | | 5(x-7)=40 | | 5z-10z=45 | | y=-3/5x+b | | -1xy+2x^2+-6y^2= | | 6x^2-3xy-18y^2= | | (2/x-7)=3 | | (11b-4)-5(2b+1)=-5 | | 2x^7+2x^6-4x^5= | | (9x-9/7)+(8-x/3)=9 | | 9x+5x+3+8=11x+4+2x | | 33*w=52 | | (6x^2+22+17)/(x+3) | | w*2w-5=52 | | 2w^2-5w-17-w^2+2w-1=0 | | 2w^2-5w-17-w^2+2w-1=00 |